The production and distribution of pottery in Mycenaean Thebes, Boeotia - Andriku, Elenē; Mommsen, Hans; Maran, Joseph (The annual of the British School at Athens, 2024)
In the course of the project ‘Pottery Production and Distribution of Bronze Age Settlements of Mycenaean Greece and the Aegean’ in 1996, Mycenaean pottery from Boeotia in the Archaeological Museum of Thebes was sampled with a view to investigation by neutron activation analysis (NAA). The NAA results were published and analysed in 2002. Ongoing work with new samples and re-evaluation of pre-existing ones, in both cases deriving from several sites of the Mycenaean world, resulted in the reappraisal of the NAA results concerning the Theban material. The present work aims at the archaeological assessment of the sampled material (152 samples from 148 examples) organised into three sections according to their exact findspot: (a) the chamber tomb cemeteries at Agia Anna area (Kolonaki and Mikro Kolonaki hills) and at Ismenion Hill; (b) the House of Kadmos; and (c) habitation areas at the lower south-east and north-west part of Kadmeia Hill. This classification corresponds roughly to the chronology of the examples dated to Middle Helladic and Late Helladic II to Late Helladic IIIC Late. The bulk of the pottery sampled is Mycenaean. A few examples of Handmade Burnished Pottery are included as well as four fragments of rooftiles, an uninscribed fragment of a Linear B tablet and a clay lump intended for a tablet. Twenty-one chemical groups/subgroups/pairs have been identified. The groups assigned to Boeotia comprise numerous examples excavated mainly at the habitation areas and dated to the subphase Late Helladic IIIB2 Late. Imports from the Peloponnese, Euboea and Crete, as well as one from Corfu, have been recognised, as have pieces of unknown provenance and loners. In conclusion, five chemical groups of pottery (TheA, TanA, TheB, ThBC, TheF) are associated with varying degrees of certainty with Boeotian pottery production. Imports came mainly from the north-eastern Peloponnese in Early Mycenaean times and from Euboea in the late palatial and post-palatial periods.
Online veröffentlicht: 11. September 2024
Gesehen am 10.09.2025